Haloxylon ammodendron Bge. майқышқылды жəне минералды құрамдары - Байсалова, Ғ.Ж.; Ерқасов, Р.Ш.; Киселев, Б.Г.; Урбисинов, Ж.К. (ҚарМУ басп., 2010)
Методом газовой хроматографии изучены жирнокислотные составы различных органов надземной части Haloxylon ammodendron Bge. Определен минеральный состав зольных остатков надземной части растительного сырья с помощью эмиссионого спектрометра с индуктивно-связанной плазмой. Проведены измерения радиационного фона надземной части сырья по методике измерения активности радионуклидов в счетных образцах на сцинтилляционном гамма-спектрометре с использованием программного обеспечения «Прогресс». Fatty acid compositions of different organs of Haloxylon ammodendron Bge. overground part were studied by means of gas chromatography. Mineral content of cinder remains of overground part of vegetable raw material was determined with the help of emission spectrometer with inductively linked plasma. The radiation background of the raw material over ground part was measured according to radionuclide activity technique in counting patterns on scintillation gamma spectrometer with the help of «Progress» software.
Fatty acid and mineral contents of Haloxylon ammodendron Bge.
Keywords: Қазақстанның флорасы; өсімдік; сексеуіл; Haloxylon ammodendron Bge.; биологиялық белсенді зат; алкалоид; фармацевтика